Fondaparinux vs warfarin for the treatment of unsuspected pulmonary embolism in cancer patients - Amato B; Compagna R; Rocca A; Bianco T; Milone M; Sivero L; Vigliotti G; Amato M; Danzi M; Aprea G; Gallelli L; de Franciscis S; et al. (Drug Design, Development and Therapy, 2016)
Bruno Amato,1,2,* Rita Compagna,1,2,* Aldo Rocca,2 Tommaso Bianco,2 Marco Milone,2 Luigi Sivero,2 Gabriele Vigliotti,2 Maurizio Amato,2 Michele Danzi,2 Giovanni Aprea,2 Luca Gallelli,3,* Stefano de Franciscis,1,4,* Raffaele Serra1,4,* 1Interuniversity Center of Phlebolymphology, International Research and Educational Program in Clinical and Experimental Biotechnology, University Magna Graecia of Catanzaro, Viale Europa, Catanzaro, 2Department of Clinical Medicine and Surgery, University of Naples “Federico II”, Naples, 3Department of Health Sciences, 4Department of Medical and Surgical Sciences, University of Catanzaro, Catanzaro, Italy *These authors contributed equally to this work Introduction: In cancer patients, the chest computer tomography (CT) can be used to identify asymptomatic pulmonary embolism (APE). In most cases, these patients are treated with anticoagulant drugs for at least 3 months. The American College of Physicians recommend treatment of these patients as patients with symptomatic pulmonary embolism. In this study, we evaluated and compared the efficacy and safety of fondaparinux vs warfarin in the prevention of unsuspected pulmonary embolism in patients with active cancer. Materials and methods: A prospective and parallel group study was performed on 64 cancer patients (29 males and 35 females) with APE. A multidetector CT angiography with high spatial and temporal resolution and quality of arterial opacification was used to make the diagnosis. Lung scintigraphy was reserved to selected patients only. Patients were randomized to either the warfarin (Group A) or the fondaparinux (Group B) for 90 days. The first end point of efficacy was the persistence, reduction, or disappearance of thrombosis after 90 days. The second end point was the reappearance of thrombosis after 1 year. The first end point of safety was the development of major bleeding. Results: We enrolled 32 patients into each treatment group. We reached the first end point of efficacy and safety in Group B which showed that fondaparinux was able to induce the disappearance of thrombotic pulmonary with a lower incidence of major bleeding events compared with warfarin. No difference in the secondary end point was recorded. Conclusion: We suggest that the treatment of cancer patients with APE can be oriented with the administration of a standard dose of fondaparinux until the next CT lung control (3 months). However, the lack of a randomized clinical trial, including a larger patient cohort, does not allow formulation of final recommendations in these patients. A broader study would be desirable, involving a larger number of patients and a longer follow-up period. Keywords: cancer patients, asymptomatic pulmonary embolism, fondaparinux, warfarin